Quality of Work Life (QWL) and Pandemic Burnout of WFO Worker - Ike Syamsiah Saputri; Badril Mutsbit; Tri Ratnawati (Profesional Muda Cendekia Publishing, 2023)
A pandemic that lasts continuously and without clarity can result in the emergence of several symptoms of pandemic burnout in the community, especially employees. A prolonged pandemic can also affect the level of quality of work-life or what is commonly called Quality of work-life (QWL). QWL is one of the factors that affect employee burnout, especially for employees who work on a WFO basis. This study aims to analyze the description of Quality of work-life (QWL) in the Pandemic Burnout of WFO Workers. This article was compiled by researchers using a qualitative type of research using the literature study method (library study). The data in this study were sourced from secondary data in the form of scientific articles. The articles obtained were then analyzed using content analysis techniques to analyze and understand the contents of the articles. The results of this study indicate that Quality of work-life (QWL) is one of the factors that significantly affect pandemic burnout in employees who work during WFO.